Asymmetry in frontcrawl swimming with and without hand paddles - Lauder, M.; Newell, R. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The aim of this study was to determine whether asymmetry exists in underwater front crawl stroking patterns with and without hand paddles. Six senior national level male swimmers performed trials at 100m race pace, with and without large (480cm2) hand paddles. Underwater motions for both right and left arms were filmed from the front and sides using three gen-locked video cameras and the video recordings were digitised at 50Hz to give three-dimensional coordinate data for a three segment model of the arm. The use of hand paddles significantly altered key temporal and kinematic features of the front crawl arm stroke for the left and right sides of the body. Specifically, the paddles increased time to complete the upsweep phase of the stroke on both sides. The paddles significantly reduced backward hand displacement on the left and right sides and altered the depth and lateral displacement of the stroke on the right side. Depth of stroke and elbow angle was also different without paddles on the right side and indicated asymmetry in technique, perhaps related to preferred breathing side.